Ethnic Minorities’ Migration Trends in the Central Highlands - Viet Hung, Ha (VNU Journal of Science: Policy and Management Studies, 2019)
Migration of the ethnic minorities in the Central Highlands is a big concern of the policymakers as well as the social researchers. The analysis of the data from two Vietnam internal migration surveys taken in 2004 and 2015 shows that the Central Highlands was a destination for the majority of rural ethnic minorities’ migrants. The study shows that the size of voluntary migrants to the Central Highlands has been strongly decreasing over the last five years. In contrast, there appeared an increasing group of voluntary migrants from the Central Highlands to other regions, especially the North-East, looking for jobs to enhance income for their households. The number of rural-urban migrants is increasing while the number of rural-rural migrants is decreasing. The share of temporary migrants is becoming dominant over that of the permanent ones in both in- and out-migration in the Central Highlands. The main purpose of the movement is job seeking and income enhancing. The analysis of the existing data sets shows a significant impact of migrants’ education on their decision of movement. The study results may contribute to the forecasting of the migration trend and serve as evidence for the ethnic minorities policymaking for the period from now to 2030.